Different Types of Investor Reactions to Annual Reports. Issue 3 (19th February 2020) - Li, Zhuwei; Wang, Baolu; Fu, Yuan; Shi, Yongdong; Su, Xuexin
ABSTRACT: This study analyzes the different investor behaviors after the release of annual reports and their reactions to revenue information. Accordingly, we use a unique dataset of account information for all shareholders in China's Shenzhen Stock Exchange. Our results indicate that individual investors are apt to increase their positions after the release of the annual report, whereas institutional investors do the opposite. Moreover, we determine that institutional investors tend to buy shareholdings after obtaining positive revenue information, whereas the behavior of individual investors is the opposite. We assume that their different degrees of overconfidence lead to different behaviors after the annual reports and revenue information are released. Evidently, individual investors are more overconfident than institutional investors.